TWINS OF LATGALE: ASSOCIATIONS AND LANGUAGE - Markus, Dace; Bukša, Ilona; Daume, Santa (Via Latgalica, 2017)
The aim of the study is to offer initial materials of the associative research done in two twin families living in Latgale and speaking Latgalian dialect. In order to get deeper knowledge about Latgalian children’s language in general, sustained and quantitative studies have to be carried out in the future. In folklore and tribal traditions (mostly in Africa) that have survived to our days, human twins are considered taboo regardless of how identical they look. In some tribal traditions, the birth of twins is received as a good omen, but in some other, on the contrary, as a serious curse. Twins are even killed and their mothers deported (Lash 1993:5). Anyway, the birth of twins is considered a creation of incomprehensible power. In this article we will use stories and drawings of twins from two families in Latgale about the following concepts: happiness, unhappiness, young, old, hard work, laziness, Latvia, the world, Europe, freedom, President, crisis, homeland, Latgale. The drawings of twins reflect every child’s meaningful associations with his/her particular understanding of the concept. These signs appear in the drawing of the selected object or component, such as the old house and the new house, a cage, where a person can escape from, a pack in the hands of a hardworking man, President’s red tie, etc. It is also seen in the posture of the person depicted in the drawing, such as with hands raised in a cheerful leap into freedom or bended legs in a dance, as well as in one’s facial expression. The drawings and narration of twins from one family are more alike when children illustrate abstract concepts. In such cases they use their knowledge about the surrounding world which is learned from TV or pictures they have seen. For instance, the seven-year-old twins colour their country Latvia in the colours of the national flag of Latvia. The earth is represented in the colours of the globe - the blue and green – and it is in the shape of the globe. The President is depicted as a solemn person in a neutral pose wearing a black suit with a red tie. Europe is shown as a formless green area. Meanwhile, the children are more careful and detailed when showing the concepts which are connected with certain things, emotions and actions, for example, a hardworking person is one who brings in fire-wood, happiness is to get a LEGO box when you want to play, a shopping-bag full of various newly purchased items. The twins also more describe those concepts, which are heard from adults, for example, why Daugavpils has such a name.The most important differences are observed in those narratives and drawings of twins from one family where the child’s emotional associations are felt. For example, when depicting freedom, the child draws a grid and thinks how to escape from it or draws freedom as a happy man who is jumping or dancing. The children’s association about the concept of old is also different. One of the twins associates this concept with the time span and draws a clock, but the other twin, thinks of ancient times and draws an antique flag with a coat of arms in the centre. The twins also understand the concept of homeland differently – one equals it to the family, but the other twin thinks his homeland is Latvia. In general, we can acknowledge that the narratives and drawings of Latgale twins confirm the cognition that twins may be similar and not similar but never alike (Lash 1993:5-6).